Adjusting to trade policy reform - Matusz, Steven J. (Policy research working paper, 1999)
A survey of more than 50 empirical papers shows that the adjustment costs of trade liberalization are small relative to the benefits. Moreover, manufacturing employment typically increases with trade liberalization. The limited data suggests that trade liberalization reduces poverty